Battery with P2-type layered oxide material as negative electrode
By using P2-type layered oxide material as the negative electrode material in sodium ion batteries, the problems of insufficient safety and performance of the negative electrode material of existing sodium ion batteries are solved, and the battery performance with high magnification, long cycle and low expansion rates are achieved, which is suitable for large-scale energy storage applications.
Patent Information
- Application Number
- CN202411950782.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The negative electrode materials of existing sodium ion batteries, especially hard carbon materials, have extremely low discharge platforms, resulting in high safety risks, fast capacity decay, poor rate-based performance, and difficult to meet the needs of large-scale energy storage.
P2-type layered oxide material is used as the negative electrode material, and the chemical formula is CaTiSnNaxMO2, where M is a transition metal element, 0.4
It improves the circulation performance and rate performance of the negative electrode of sodium ion battery, reduces the risk of sodium analysis, enhances the safety and energy density of the battery, and is suitable for large-scale energy storage applications.
Smart Images

Figure CN119764439A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of batteries, and in particular relates to a battery using a P2 type layered oxide material as a negative electrode. Background Art
[0002] As the world develops, people are increasingly concerned about the depletion of fossil fuels, and methods for developing and utilizing green and sustainable energy are becoming increasingly important. At present, green energy such as solar energy and tidal energy have gradually attracted attention from all walks of life because of their environmental protection and sustainability, but disadvantages such as voltage instability have limited their application. Therefore, large-scale energy storage devices have been introduced and developed rapidly. In recent years, although lithium-ion batteries have been widely used in some energy storage devices in the automotive industry and power grid systems, with the rise of the lithium battery industry, the lithium resources on the earth are also gradually decreasing. The limited availability of lithium has led to an increase in material costs after the widespread commercialization of lithium. On the contrary, sodium is abundant in the earth's crust and is considered to be a low-cost battery. At present, research on sodium batteries focuses on positive electrode materials, such as layered oxides, polyanions, Prussian blue and other positive electrode materials have been widely used, while research on negative electrodes is less. The negative electrode materials with a high degree of application at present are carbon materials such as hard carbon and soft carbon. Although materials such as hard carbon show good electrochemical properties, most of the capacity is distributed between 0-0.1V. This extremely low discharge platform will cause the negative electrode to easily form Na dendrites, causing serious safety problems. Although the initial specific capacity of hard carbon is high, its capacity will decay rapidly with the increase of cycles, affecting the service life of the entire battery cell. At the same time, this material has poor rate capability due to its interlayer insertion sodium storage. Therefore, developing new negative electrode materials to improve the performance of sodium-ion batteries is an important direction of current battery technology research. Summary of the invention
[0003] In view of this, the present invention aims to overcome the defects in the prior art and proposes a battery using a P2-type layered oxide material as a negative electrode.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0005] A P2-type layered oxide material, the chemical formula of which is CaTiSnNa x MO2, where M is a transition metal element, 0.4<x<0.8. The sodium ions in the P2-type layered oxide material are in triangular prism coordination, and the stacking mode of (M02)n is two layers, in which some Na sites are replaced by trace amounts of Ca, Ti and Sn, forming a chemical formula of CaTiSnNa xMO2's P2-type sodium-deficient layered oxide material is doped with some elements such as Ca and Sn compared to traditional P2 positive electrode oxide materials. The addition of such elements is beneficial to increase the interlayer spacing, increase the Na ion diffusion channel, and improve the rate performance. At the same time, this element will also increase the stability of the overall structure of the material, thereby improving the cycle performance of the battery cell. The introduction of Ti can provide more sites for Na ions, which is beneficial to the improvement of sodium embedding capacity. Applying this material to the negative electrode of sodium ion batteries not only stabilizes the attenuation of the capacity of the hard carbon negative electrode, but also improves the overall rate performance of the battery cell. This material has a high voltage platform, no risk of sodium precipitation at the negative electrode, and high safety performance.
[0006] Furthermore, the M is at least two of nickel, cobalt, manganese or copper.
[0007] The present invention also provides an application of a P2-type layered oxide material in the preparation of a sodium ion battery, wherein the negative electrode material of the sodium ion battery is the P2-type layered oxide material.
[0008] The present invention also provides a battery using a P2-type layered oxide material as a negative electrode. The battery comprises a positive electrode, a negative electrode, a separator and an electrolyte. The negative electrode is the P2-type layered oxide material.
[0009] Furthermore, the positive electrode is at least one of the P2-type layered oxide material, 03 layered oxide, polyanion material or Prussian blue material.
[0010] Furthermore, the diaphragm is at least one of polypropylene, polyethylene or fiber diaphragm.
[0011] Furthermore, the electrolyte is an electrolyte containing sodium ions; the electrolyte is at least one of NaPF6 or NaClO4; the solvent of the electrolyte is a carbonate solvent or an ether solvent; the solvent of the electrolyte is 1,3-dioxane or ethyl acetate.
[0012] Furthermore, the packaging material of the battery is an aluminum-plastic composite material or a metal material.
[0013] Furthermore, the battery is assembled by winding or lamination.
[0014] The present invention also provides a method for preparing a battery using a P2-type layered oxide material as a negative electrode, comprising the following steps: assembling a positive electrode sheet, a negative electrode sheet and a separator into a dry battery cell by winding or stacking, then drying and shelling, injecting an electrolyte, chemically dividing the cells, and then conducting an electrical performance test.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] The unique structure of the P2-type layered oxide material of the present invention makes it have excellent rate performance, and this material hardly undergoes phase change during the insertion and extraction of Na ions, which is beneficial to improving the cycle life of the battery. The positive electrode used in the battery can use P2, O3 layered oxides, polyanions, and Prussian blue as the positive electrode material of the sodium ion battery.
[0017] The battery structure using the P2-type layered oxide material as the negative electrode of the present invention has the advantages of long cycle, high rate and low expansion rate, and is suitable for large-scale storage applications.
[0018] The battery with the P2-type layered oxide material as the negative electrode can improve the rate performance and cycle performance of the battery, and because its preparation process is relatively simple and easy to achieve large-scale production, it has broad application prospects. In addition, the high stability and low volume expansion characteristics of the material make it an ideal choice for large-scale energy storage systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a capacity-voltage curve at room temperature of the sodium ion battery cell described in Example 1 of the present invention. DETAILED DESCRIPTION
[0020] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0021] The present invention will be described in detail below with reference to the embodiments.
[0022] Example 1
[0023] A method for preparing a battery using a P2-type layered oxide material as a negative electrode comprises the following steps:
[0024] (1) P2-type layered oxide material CaTiSnNa 0.6 FeMnO2, conductive agent SP, conductive agent CNTs, and binder PVDF5130 were mixed in a mass ratio of 95:1.5:1.5:2 and homogenized using NMP solvent. After the slurry was prepared, it was wet-coated on the surface of 12μm aluminum foil with a double-sided surface density of 30mg / cm 2 ;
[0025] (2) The above CaTiSnNa 0.6 FeMnO2 pole piece is rolled and compacted to a density of 3g / cm 3; The qualified electrode sheets are cut into strips and slices to prepare the required negative electrode sheets. The peeling force of the electrode sheet is 30N / m and the film resistance is 26Ω*cm;
[0026] (3) preparing a sodium nickel iron manganese oxide positive electrode sheet in the same manner;
[0027] (4) The positive and negative electrode sheets and the separator are wound together into a cylindrical core, the core is baked, and after the moisture content is qualified, the core is shelled, the electrolyte is injected, and the core is packaged into a battery cell.
[0028] Example 2
[0029] A method for preparing a battery using a P2-type layered oxide material as a negative electrode comprises the following steps:
[0030] (1) P2-type layered oxide material CaTiSnNa 0.6 FeMnO2, conductive agent SP, conductive agent CNTs, and binder PVDF5130 were mixed in a mass ratio of 95:1.5:1.5:2 and homogenized using NMP solvent. After the slurry was prepared, it was wet-coated on the surface of 12μm aluminum foil with a double-sided surface density of 30mg / cm 2 ;
[0031] (2) The above CaTiSnNa 0.6 FeMnO2 pole piece is rolled and compacted to a density of 3g / cm 3 ; Slitting and cutting the qualified electrode sheets after rolling into the required negative electrode sheets;
[0032] (3) The O3-type layered oxide material sodium nickel cobalt manganese oxide, the conductive agent SP, the conductive agent CNTs, and the binder PVDF5130 were mixed in a mass ratio of 95:1.5:1.5:2, and homogenized using NMP solvent. After the slurry was prepared, it was wet-coated on the surface of a 12 μm aluminum foil, and the double-sided surface density was 30 mg / cm 2 , the electrode sheet is used as the positive electrode sheet of the battery cell;
[0033] (4) The positive and negative electrode sheets and the separator are wound together into a cylindrical core, the core is baked, and after the moisture content is qualified, the core is shelled, the electrolyte is injected, and the core is packaged into a battery cell.
[0034] Example 3
[0035] A method for preparing a battery using a P2-type layered oxide material as a negative electrode comprises the following steps:
[0036] (1) P2-type layered oxide material CaTiSnNa 0.6FeMnO2, conductive agent SP, conductive agent CNTs, and binder PVDF5130 were mixed in a mass ratio of 95:1.5:1.5:2 and homogenized using NMP solvent. After the slurry was prepared, it was wet-coated on the surface of 12μm aluminum foil with a double-sided surface density of 30mg / cm 2 ;
[0037] (2) The above CaTiSnNa 0.6 FeMnO2 pole piece is rolled and compacted to a density of 3g / cm 3 ; Slitting and cutting the qualified electrode sheets after rolling into the required negative electrode sheets;
[0038] (3) The polyanion positive electrode material sodium iron phosphate pyrophosphate, the conductive agent SP, the conductive agent CNTs, and the binder PVDF5130 were mixed in a mass ratio of 95:1.5:1.5:2, and homogenized using NMP solvent. After the slurry was prepared, it was wet-coated on the surface of a 12 μm aluminum foil, and the double-sided surface density was 30 mg / cm 2 , the electrode sheet is used as the positive electrode sheet of the battery cell;
[0039] (4) The positive and negative electrode sheets and the separator are wound together into a cylindrical core, the core is baked, and after the moisture content is qualified, the core is shelled, the electrolyte is injected, and the core is packaged into a battery cell.
[0040] Comparative Example 1
[0041] A method for preparing a battery using a P2-type layered oxide material as a negative electrode comprises the following steps:
[0042] (1) Put Na 0.6 FeMnO2, conductive agent SP, conductive agent CNTs, and binder PVDF5130 were mixed in a mass ratio of 95:1.5:1.5:2 and homogenized using NMP solvent. After the slurry was prepared, it was wet-coated on the surface of 12μm aluminum foil with a double-sided surface density of 30mg / cm 2 ;
[0043] (2) The above Na 0.6 FeMnO2 pole piece is rolled and compacted to a density of 3g / cm 3 ; Slitting and cutting the qualified electrode sheets after rolling into the required negative electrode sheets;
[0044] (3) Prepare sodium ferromanganate positive electrode sheet in the same way;
[0045] (4) The positive and negative electrode sheets and the separator are wound together into a cylindrical core, the core is baked, and after the moisture content is qualified, the core is shelled, the electrolyte is injected, and the core is packaged into a battery cell.
[0046] Comparative Example 2
[0047] A method for preparing a battery using a P2-type layered oxide material as a negative electrode comprises the following steps:
[0048] (1) CaNa 0.6 FeMnO2, conductive agent SP, conductive agent CNTs, and binder PVDF5130 were mixed in a mass ratio of 95:1.5:1.5:2 and homogenized using NMP solvent. After the slurry was prepared, it was wet-coated on the surface of 12μm aluminum foil with a double-sided surface density of 30mg / cm 2 ;
[0049] (2) The above CaNa 0.6 FeMnO2 pole piece is rolled and compacted to a density of 3g / cm 3 ; Slitting and cutting the qualified electrode sheets after rolling into the required negative electrode sheets;
[0050] (3) Prepare calcium sodium iron manganate positive electrode sheet by the same method;
[0051] (4) The positive and negative electrode sheets and the separator are wound together into a cylindrical core, the core is baked, and after the moisture content is qualified, the core is shelled, the electrolyte is injected, and the core is packaged into a battery cell.
[0052] Comparative Example 3
[0053] A method for preparing a battery using a P2-type layered oxide material as a negative electrode comprises the following steps:
[0054] (1) NaFeO2 (layered rock type α-NaFeO2), conductive agent SP, conductive agent CNTs, and binder PVDF5130 were mixed in a mass ratio of 95:1.5:1.5:2, and slurried using NMP solvent. After the slurry was prepared, it was wet-coated on the surface of 12 μm aluminum foil with a double-sided surface density of 30 mg / cm 2 ;
[0055] (2) The above-mentioned pole piece is rolled and the compaction density is 3g / cm 3 ; Slitting and cutting the qualified electrode sheets after rolling into the required negative electrode sheets;
[0056] (3) Prepare the positive electrode sheet in the same way;
[0057] (4) The positive and negative electrode sheets and the separator are wound together into a cylindrical core, the core is baked, and after the moisture content is qualified, the core is shelled, the electrolyte is injected, and the core is packaged into a battery cell.
[0058] The batteries obtained in Examples 1-3 and Comparative Examples 1-3 were tested, and the results are shown in Table 1.
[0059] Table 1 Results
[0060] project Cycle performance Rate performance Expansion rate Example 1 2000 4C 15% Example 2 1800 4C 15% Example 3 2000 2C 20% Comparative Example 1 1000 3C 15% Comparative Example 2 800 3C 15% Comparative Example 3 1000 2C 20%
[0061] As shown in Table 1, CaT i SnNa 0.6 FeMnO2, in the original Na 0.6 FeMnO2 is doped with elements such as Ca, Ti and Sn. The addition of Ca and Sn is beneficial to increase the interlayer spacing, increase the Na ion diffusion channel, and improve the rate performance. At the same time, the element will also increase the stability of the overall structure of the material, thereby improving the cycle performance of the battery. The introduction of Ti can provide more sites for Na ions, which is beneficial to the improvement of sodium embedding capacity. Therefore, it can be seen from Table 1 that Example 1 using this negative electrode has the best cycle and rate performance. At the same time, the expansion rate of the battery is low, and the smaller volume change is beneficial to improve the overall energy density of the battery and reduce the cost of the battery.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A P2-type layered oxide material, characterized in that: The chemical formula of this material is CaTiSnNa x MO2, wherein M is a transition metal element, 0.4<x<0.
8.
2. The P2-type layered oxide material according to claim 1, characterized in that: The M is at least two of nickel, cobalt, manganese or copper.
3. Use of the P2-type layered oxide material according to claim 1 or 2 in the preparation of a sodium ion battery, characterized in that: The negative electrode material of the sodium ion battery is the P2 type layered oxide material.
4. A battery with a P2-type layered oxide material as a negative electrode, characterized in that: The battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is the P2 type layered oxide material as claimed in claim 1 or 2.
5. The battery using the P2-type layered oxide material as the negative electrode according to claim 4, characterized in that: The positive electrode is at least one of the P2-type layered oxide material, 03 layered oxide, polyanion material or Prussian blue material as described in claim 1 or 2.
6. The battery using the P2-type layered oxide material as the negative electrode according to claim 4, characterized in that: The diaphragm is at least one of polypropylene, polyethylene or fiber diaphragm.
7. The battery using the P2-type layered oxide material as the negative electrode according to claim 5, characterized in that: The electrolyte is an electrolyte containing sodium ions; the electrolyte is at least one of NaPF6 and NaClO4; the solvent of the electrolyte is a carbonate solvent or an ether solvent; the solvent of the electrolyte is 1,3-dioxane or ethyl acetate.
8. The battery using the P2-type layered oxide material as the negative electrode according to claim 3, characterized in that: The packaging material of the battery is an aluminum-plastic composite material or a metal material.
9. The battery using the P2-type layered oxide material as the negative electrode according to claim 3, characterized in that: The battery is assembled by winding or lamination.
10. A method for preparing a battery using the P2-type layered oxide material as a negative electrode according to any one of claims 3 to 9, characterized in that: The method comprises the following steps: assembling the positive electrode sheet, the negative electrode sheet and the separator into a dry battery cell by winding or stacking, then drying and putting the cells into a shell, injecting electrolyte, chemically dividing the cells into different capacities, and then conducting an electrical performance test.
Citation Information
Cited By
Sodium ferric phosphate pyrophosphate material of high-voltage platform, positive pole piece, battery cell and preparation method of sodium ferric phosphate pyrophosphate material
CN120600794A